Evaluation of shear bond strength of orthodontic resin and resin modified glass ionomer cement on bonding of metal and ceramic brackets - Rosana Costa Casanovas de Carvalho; Natália Maria Porto de Carvalho; Synara Santos Herênio; José Roberto de Oliveira Bauer; Antonio Ernandes Macedo Paiva; José Ferreira Costa; Elizabeth Lima Costa (Revista Sul-Brasileira de Odontologia, 2013)
The aim of this study was to evaluate the shear bond strength of orthodontic resin and resin-modified glass ionomer cement on bonding of metal and ceramic brackets. Material and methods: Forty bovine teeth were sectioned and embedded into PVC with chemically-cured acrylic resin. The labial surfaces were flattened and received prophylaxis with pumice and water. Then they were divided into four groups, according to the bonding material and the type of bracket. Group 1: metallic bracket + Transbond XT; Group 2: metallic bracket + Vitremer; Group 3: ceramic bracket + Transbond XT; Group 4: ceramic bracket + Vitremer. The bonding was performed according to the manufacturers’ recommendations. The shear bond strength test was conducted in a universal testing machine (TIRAtest 2420) at a crosshead speed of 0.5 mm/min. Then, the fractured surfaces were evaluated using a stereomicroscope (x15 magnification) to check the adhesive remnant index. Data was subjected to two-way ANOVA and Tukey’s test for pairwise comparisons (α = 0.05). Results: The results suggested a non-significant effect of the interaction (p > 0.97), and only main factors were significant (p = 0.0001). The bond strength of Transbond XT was statistically higher than Vitremer. Ceramic brackets obtained the highest values of resistance when compared with metal brackets. Conclusion: The ceramic brackets bonded with Transbond XT orthodontic resin have excellent bond strength results.